Analisis segmentasi, target dan posisi pasar produk gadai (rahn) pada bank kaltimtara syariah kota samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Analysis of Segmentation, Target and Position of Pawn Product Market (rahn) at Bankaltim Syariah of Samarinda City under the guidance of Dr. Hj. Rahmawati, S.E., MM and Mr. Robiansyah, S.E., M. Sc.The purpose of this study was to determine the analysis of the marketing strategy of pawn products (rahn) with the STP method (Segmentation, Target and Position) at the Bankaltim Syariah Branch of Samarinda City.This study used cluster analysis tools and was also assisted by computerized statistical product and service solutions (SPSS) program version 22.0. The type of data used is Primary Data and Secondary Data contained in Bankaltim Syariah Branch of Kota Samarinda.